Induction of flowering by girdling to advance the ‘Hass’ avocado harvest in Nayarit, Mexico - Sánchez-Hernández, Esperanza; Alejo-Santiago, Gelacio; García-Paredes, Juan Diego; Sánchez-Hernández, Rufo; Aburto-González, Circe Aidín; Ramírez-Guerrero, Leobarda Guadalupe; Balois-Morales, Rosendo (REVISTA TERRA LATINOAMERICANA, 2020)
Among the difficulties of the ‘Hass’ avocado production in Nayarit are the low prices derived from seasonality of the harvest in the months ranging from September to November. The objective of our research was to identify the girdling date capable of advancing the flowering and thereby advancing the harvest season. Four girdling dates (treatments) were evaluated in ten replicates under a completely randomized experimental block design, generating the following treatments (T) during 2017: T1 = August 15, T2 = September 15, T3 = October 15, T4 = November 15 and T5 (without girdling). Each ring was 0.5 cm wide and disposed in 50% of the branches. The variables evaluated were the following: concentration of N, P, K, Ca and Mg in vegetative and flowering stages, days at the beginning of flowering, number of flower buds per m3 of canopy, days at the beginning of fruiting, panicle length, panicle thickness, fruit production per tree and dry matter of mesocarp. The analysis of variance showed significant differences for days at the beginning of flowering, days at the beginning of fruiting, panicle length, dry matter in mesocarp and fruit production. There were no differences in nutritional concentration at the phenological stages. We concluded that August 15 was the girdling date that advanced flowering by 52 days compared to T5, and allowed the harvest to be performed in May.